Aging and sexuality. Issue 4 (2nd September 2019) - Childs, Jr, James M.
Abstract: Many see old age as asexual but studies show that significant numbers of people 65 years old and older continue to desire and engage in acts of sexual intimacy as seem in long‐term care facilities and in cohabitation. Sexual ethics in the context of aging requires respect for the sexuality of older adults and sensitivity to their needs and challenges.